La bohème opera in four acts - Puccini, Giacomo 1858-1924 (Naxos Media Holdings (Europe), 2017)
Based on stories by Henri Murger but also infused with the composer's own experiences as a penniless graduate, Puccini's powerful opera that portrays its youthful characters' romantic outlook on life and the brutally tragic end to their innocence. The story is set around 1830 but director Orpha Phelan sees Puccini's characters as equally at home in our times
Interpreten: Olesya Golovneva (Mimi). Marioa Fontosh (Musetta). Joachim Bäckstöm (Rodolfo). Vladislav Sulimsky (Marcello). Daniel Hällström (Schaunard). Miklós Sebestyén (Colline). supporting soloists. Malmö Opera Orchestra and Chorus. Christian Badea (Dirigent)
Aufnahme: 18. Mai 2014
Bildformat: 16:9
Based on: Scènes de la vie de bohème / Henri Murger
Performer notes and synopsis in English (15 pages : portraits) inserted in container
Keywords: Operas; Filmed performances; Feature films; Film; Blu-Ray-Disc